Serviços para Publicação e Recuperação de Componentes de Software através da Internet em Ambientes de Reuso - Souza, Robson Pinheiro de; Werner, Cláudia M. L.; Mattoso, Marta L. Q. (Anais Estendidos do Simpósio Brasileiro de Engenharia de Software (SBES), 2000)
Component-based software development aims at constructing new systems from reusable components. Some studies have concluded that reuse increases both quality and productivity of software developments. Amongst the problems involved in the application of reuse techniques, two of them are treated in this work: (i) the difficulty of locating and retrieving components stored in heterogeneous repositories spread over the Internet; and (ii) the problem of publishing new components, in order to help both their integration to a reuse environment and comprehension by the developer. Aiming at supporting the solution of the two mentioned problems, this work proposes a component integration layer to a reuse infrastructure. In our research, we aim to explore and to associate the features of two different technologies: (i) the new technology of interoperability systems, in particular the LeSelect system, in order to solve the existing problems of interoperability between repositories of components; (ii) the popular technology of mediators, responsible for managing XML metadata extracted from each repository, providing transparency in the location and retrieval of components, and services for query optimization.